ALIH KODE, CAMPUR KODE, DAN IDENTITAS SOSIAL DALAM FILM YOWIS BEN SERIES: KAJIAN SOSIOLINGUISTIK - Vioni Yohana Mayzahra; Kania Putri Niken Zarani; Syahrul Ramadhan; Elfia Sukma; Norliza Jamaluddin (Prakata: Jurnal Bahasa dan Sastra Indonesia Serta Pembelajaran, 2025)
This research analyzes the phenomenon of code-switching and code-mixing and its relationship with social identity in the Yowis Ben series. This study aims to identify the forms of code-switching and code-mixing and explain how these language variations represent the social identity of the characters. The data in this study were collected using the listening technique (observation of conversations in the film) and the note-taking technique (transcripts of dialogs with code-switching and code-mixing elements). The results show that code-switching and code-mixing in Yowis Ben Series occur between Javanese, Indonesian, and English, which are influenced by situation, context, and social. The use of these language variations not only functions as a means of communication, but also reflects the character's identity, such as ethnicity, social class, and generation. This finding strengthens the view that language choice in interactions between characters in the Yowis Ben series can be a marker of the identity of a multilingual society.